THE TRICKSTER ARCHETYPE IN CONTEMPORARY MEDIA: LUCIFER MORNINGSTAR AND NOLAN BOOTH - Zacharia, Rosmy Ann; Sreena K. (International Journal of Research -GRANTHAALAYAH, 2025)
This paper explores the representation and reinterpretation of the trickster archetype in contemporary media through a psychoanalytic reading of Lucifer Morningstar from the Netflix series Lucifer and Nolan Booth from the Netflix film Red Notice. This study utilizes Carl Jung’s theory of archetypes as a major framework and specifically focuses on the trickster archetype to identify the characters cunning strategies moral complexity and disruptive tendencies that impacts narrative development. By comparing Lucifer and Nolan, the paper highlights the Tricksters adaptability in modern storytelling showcasing its role as both a source of chaos and an agent of change. Furthermore, this analysis explores how contemporary media reshapes archetypal roles bridging the gap between traditional psychological theories and present-day narrative structures.